Complications and Morbidity associated with Loop Ileostomies in Patients with Ulcerative Colitis. (March 2018) - Park, J.; Gessler, B.; Block, M.; Angenete, E.
Background and Aims: Loop ileostomies are frequently used as diversion of the fecal stream to protect a distal anastomosis. The aim of this study was to identify complications and morbidity related to loop ileostomies in patients with ulcerative colitis at a nonemergent setting. Material and Methods: Consecutive patients with ulcerative colitis who received a loop ileostomy at a tertiary referral center in Sweden from January 2006 until December 2012 were included and studied retrospectively. Results: In total, 71 patients were identified, and the median age was 39 years. A majority (94%) of the patients underwent proctectomy or proctocolectomy with primary construction of an ileal pouch–anal anastomosis. In total, 38 patients (54%) had one or more postoperative complications at index surgery. Stoma-related complications were seen in 49% where parastomal skin irritation was most common. In total, 18% of the patients were re-admitted due to morbidity related to the ileostomy, and the leading cause was high volume output. Complications related to closure were seen in 29% of the patients, and of these, 30% required surgical intervention. In total, five patients (7%) developed a symptomatic leakage in the ileo-ileal anastomosis. There was no mortality. Conclusion: Loop ileostomies in this young patient cohort resulted in considerable morbidity. Closure of the ileostomy was also associated with complications. Although the diverting loop ileostomy is constructed to decrease the clinical consequences of an anastomotic leakage, the inherent morbidity should be considered. Preventive measures for parastomal skin problems could improve results.